GETTING TO KNOW YAHOWU AND YA’AHOWU WARM GREETINGS FROM THE NIAS COMMUNITY - Harefa, Darmawan (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Language and culture play a crucial role in shaping the identity of a community. In Nias society, the greetings "Yahowu" and "Ya’ahowu" serve as distinctive forms of address that reflect warmth, blessings, and deeply held social values. Although these greetings are often considered to have the same meaning, there are differences in their usage across social, religious, and customary contexts. This study aims to examine the meaning, distinctions, and cultural significance of "Yahowu" and "Ya’ahowu" in the daily life of the Nias people. Through a qualitative approach involving literature studies and interviews with local community members, the findings indicate that "Ya’ahowu" is more commonly used in formal, customary, and religious settings, whereas "Yahowu" is more prevalent in everyday conversations. These greetings are not merely forms of communication but also serve as cultural identity markers that reinforce social solidarity and local wisdom within the Nias community. This study is expected to enhance understanding and appreciation of Nias cultural heritage and emphasize the importance of preserving traditional values in the modern era.